WORK LIFE BALANCE AND WORK FAMILY CONFLICT ON TEACHER PERFORMANCE IN SD PLUS RAHMAT KEDIRI - H R, Mochammad Ryan; Jatmiko, Udik (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 3 No 02 (2023): EDISI JUNI - SEPTEMBER 2023DO - 10.32503/ammer.v3i02.4364, 2023)
The problem of this research is the phenomenon of the lack of performance of SD Plus Rahmat Kediri teachers which is affected by the problem of working time balance with family. This study aims to determine the effect of Work-Life Balance and Work-Family Conflict on Teacher Performance at SD Plus Rahmat Kediri either partially or simultaneously. This type of research is quantitative by using the Critical Case Sampling method purposive sampling technique according to the criteria of researchers as many as 56 respondents and using interview research methods, observation, questionnaires, documentation, and literature study. For data analysis techniques in this study using the validity test, reliability test, classic assumption test, multiple linear regression test, t-test, F test, test the coefficient of determination (RÂ²) . the results of the t-test variable Work-Life Balance (X1) had a partially significant effect on teacher performance by obtaining a sig. 0.000 <0.050 and the variable Work-Family Conflict (X2) has no partially significant effect on teacher performance by obtaining a sig. 0.770 < 0.050. Meanwhile, the results of the F test showed that Work-Life Balance (X1) and Work-Family Conflict (X2) have a significant simultaneous effect on the performance of SD Plus Rahmat Kediri Teachers with a Sig. 0.000 < 0.05.